The Fractured Annexation: The historical reasons for the separation of Paquera, Cóbano and Lepanto from the Province of Guanacaste - Solano Muñoz, Edgar (2025)
The aim of this article is to analyze the historical reasons behind the administrative separation of Guanacaste from the territories of Paquera, Lepanto and Cóbano, carried out by the 1864 census. The notion of territoriality was used for the study, and municipal sources were used for support. It is concluded that the segregation of the territories of the Nicoya Peninsula was due to the interest of the coffee-growing oligarchy to support the port of Puntarenas during the 19th century and ensure the export of coffee; as well as to consolidate the commercial activity of Costa Rica.